Correction: Myoglobin regulates fatty acid trafficking and lipid metabolism in mammary epithelial cells. - Julia Armbruster; Mostafa A Aboouf; Max Gassmann; Angela Egert; Hubert Schorle; Veit Hornung; Tobias Schmidt; Jonathan L Schmid-Burgk; Glen Kristiansen; Anne Bicker; Thomas Hankeln; Hao Zhu; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0275725.].